Concurrency exercises in Go - Schlesinger, Aaron (Aaron Schlesinger, 2020)
"As Moore's law reaches its limit, CPUs are no longer getting much faster. Instead, they are expanding horizontally and adding multiple cores, each with the full features of an individual CPU. As applications move en-mass to the cloud and are expected to take advantage of powerful multi-core processors, software that does not take full advantage of all the CPUs on the server are leaving money on the table. These new requirements mean that your software will need to be concurrent by default. While concurrency strategies in older languages can lead to buggy software with hard-to-debug issues like race conditions, Go takes a different approach. In these screencasts, you'll learn how Go's concurrency works by example. Each screencast will solve a concurrency challenge using best practices and the built-in Go concurrency tools. In the process, you'll learn how to best do concurrency in the language."--Resource description page